Gas phase catalytic dehydrochlorination and hydrodechlorination of aliphatic and aromatic systems - Tavoularis, George; Keane, Mark A (Journal of molecular catalysis. A, Chemical, 1999)
The gas phase dechlorination of cyclohexyl chloride and chlorobenzene, over the temperature range 423 K≤ T≤573 K, promoted using a silica supported nickel catalyst in the presence of hydrogen has been studied. Chlorine removal from the chloroalkane is shown to occur by dehydrochlorination via an E1 type elimination mechanism to yield cyclohexene and HCl as the products. The reaction was found to exhibit zero order behaviour with respect to hydrogen partial pressure, a temperature dependent reaction order (varying from 0.4 to 0.7) with respect to the chloroalkane and an apparent activation energy equal to 115 kJ mol −1. Turnover of the cyclohexyl chloride reactant was subject to a short term loss of catalytic activity due to a surface poisoning by the HCl that was produced where the presence of hydrogen served to displace the inorganic halide and extend the productive lifetime of the catalyst. A steady state conversion of chlorobenzene was however readily achieved where dechlorination in hydrogen occurs via an electrophilic hydrodechlorination mechanism. Bromine removal from cyclohexyl bromide and bromobenzene is also considered for comparative purposes. The ease of halogen removal and process selectivity are discussed in terms of thermodynamic limitations and reactant/catalyst interactions.